STUDENTS’ PERFORMANCE AND EXPECTATION TOWARD MICRO TEACHING CLASS IN ENGLISH STUDY PROGRAM - Sofian Sofian (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2018)
This study aims to obtain accurate information about students’ performance in Micro Teaching class and how it meets the students’ expectations toward Micro Teaching class on sixth semester students of English Language Program FKIP Untan Pontianak. The method of this study was quantitative method. The subjects of this study are sixth semester students of English academic year 2017-2018 who took Micro Teaching subject. The researcher took 42 students as the samples of this study. The instruments which were used in this study were an observation sheet adopted from the observation sheet of Education and Teacher Training’s (PLPG) assessment activity and questionnaires which were designed based on Likert scales. The findings of this research was then analyzed qualitatively to find out how well the students performed in the micro teaching class, and to find out how the micro teaching class met the students’ expectations. The results of this study showed that the students’ performance in Micro Teaching is categorized as good performance regarding the minimum score of a student in this research was 3.01 which was considered successful in this subject, and it also showed that the students’ performance met the students’ expectations, it was proved by how high the students put their expectations in learning which was counted qualitatively by obtaining the average score of the interpretation scores for the whole questions in the questionnaire 87%.